MENINGKATKAN AKTIVITAS BELAJAR, KARAKTER KESADARAN LINGKUNGAN DAN HASIL BELAJAR DI SEKOLAH DASAR - Yulanda; Muhsinah Annisa (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research was shown to describe teacher activity, to analyze activity, learning outcomes and environmental awareness characters in students, leaving the STEM-based Problem Based Learning and Course Review Horay models. The method used is qualitative and quantitative in the type of Class Action Research (CAR). The research subject were fourth grade students V. The results showed that teacher activity was carried out to reach 95 with the criteria “very good”, student activity was carried out to reach 93% percetase with the criteria “very active”, students' cognitive learning outcomes reach a percentage of 100% with the criteria “complate”, the assessment of environmental awareness characters reaches a percentage of 86% with the criteria “have cultured ” and psychomotor learning outcomes reach a percentage of 93% with the criteria “very good”. The results of the study showed an increase in student activity, student learning outcomes and environmental awareness character of elementary school students.